Study of chemical component from lichen ( parmotrema praesorediosum ) / Azreen Mohd Nadzri - Mohd Nadzri, Azreen (2017)
This study represents the first identification of chemical component on Parmotrema praesorediosum from Malaysia collected in the area of UiTM Kuala Pilah, Negeri Sembilan. This species belongs to the family Parmeliaceae. Since, the healing potential of the component found in some lichen species as medical purpose has not been completely explored, therefore, numeral of method have been conducted in order to identify the presence of component found in lichen especially on Parmotrema praesorediosum species. This species was successively extracted in acetone and methanol where high percentage crude yield of methanol extract give 6.82 % compared to acetone extract which give 6.68 %. TLC technique that developed in solvent (hexane:diethyl ether:formic acid), (toluene:acetic acid) and (hexane:ethyl acetate) shows (hexane:ethyl acetate) was selected to use for the next separation due to it clear spot resolution in TLC test. The acetone extracts were subjected to column chromatography, eluted with increasing polarity of mixture solvent from (hexane:ethyl acetate) to (ethyl acetate : methanol) and collected in 70 vials. Only one vials (vials 56) is selected for further analysis based on the less spot appear in TLC plate that observed under UV lamp. Based on the spectroscopy analysis using UV spectroscopy which give maximum wavelength of λ = 215 nm, FTIR with several absorption, GC-MS with m/z 503 molecular weight and comparison from literature data, it is shown that the isolated compound from Parmotrema Praesorediosum was probably morphine 3- methyl ether.